A Scrum-Driven Software Development of IoT-Integrated Smart Trash Solution with UV-C Sterilization and Blackbox Testing - Dian Resti Juliani; Irman Hariman (Universitas Kebangsaan Republik Indonesia, 2023)
Serious challenges in waste management in Indonesia have had a significant impact on health and the environment. The excessive accumulation of waste has led to new issues, including a decline in environmental quality and the spread of diseases. This study employs a qualitative approach to address this problem. The Scrum methodology is employed in software development, with an emphasis on blackbox testing and Boundary Value Analysis (BVA). Research findings reveal issues in waste management, including excessive accumulation and bacterial growth in waste disposal sites. A proposed solution is presented through an IoT and Android-based